To study the trends of market arrivals and prices of rapeseed and mustard in Bharatpur district of Rajasthan - Singh, Hemendra; Singh, Prathvi; Bairwa, Kailash Chand (Annals of Agricultural Research, 2014)
Rapeseed-mustard (Brassica species) is the major rabi oilseed crops of India. It occupies a prominent place next to groundnut both in area and production. Rajasthan has first position, which has 2.84 million ha. area and 3.50 million tonnes production in 2008-09 (Directorate of Economics and statistics, 2009-10). It is mainly growing in Sriganganagar, Bharatpur, Alwar and Kota districts of Rajasthan. Therefore a study was carried out to assess the trend in market arrivals and prices of Rapeseed-mustard in Bharatpur district of Rajasthan. The primary and secondary data were collected from farmers and Mandi offices. a multi-stages random sampling method was used. The result was found that the higher indices for arrivals were recorded during the month of March to May (April) and lower from June to February (February). The price indices were the lowest in May and highest in February in Bharatpur market. Main factors responsible for more arrivals of rapeseed-mustard in Bharatpur market were the payment of on the same day, higher prices than other markets of the Bharatpur district, open auction method of sale, less market charges, than other market (Nadbai, Deeg, Kama etc.), store facilities for farmer's produce till the time of sale. Production and quantity sold per farm both in absolute and percentage terms increases with increase in farm size. There was positive relationship between farm size, total stock and previous stock.